Synthesis of zeolite templated graphene (ZTG) from methanol via chemical vapor deposition (CVD) method [electronic resource] - Mohd. Syafiq Elias, 1990- (2013)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2013